Applying Chaid to Identify the Accounting-Financial Characteristics of the Most Profitable Real Estate Companies in Spain - Rayo, Salvador (2010)
The aim of this study is the determination, from an empirical perspective, of the accounting and financial features which could condition financial profitability of real estate companies, to identify the performances that guarantee its permanency in the current marketplace, characterized by the world economic crisis, specially in Spain, whose housing sector represents an important contributor to the economic growth. Although at a theoretical level the DuPont Model establishes the relationships between a group of accounting ratios and financial profitability. This paper uses a sample of 5,484 Spanish real estate companies to quantify these relationships and to extract the most relevant ones and to obtain the patterns of the most profitable companies. We use ROE to measure profitability and we analyze various independent variables about solvency, liquidity, activity, turnover, financial equilibrium and investment structure. The main contribution is of methodological nature, as we have applied statistics tools that do not require initial hypotheses on the distribution of the variables, by using a data mining technique of classification and regression tree based on rule induction algorithms known as CHAID. The study provides quantitatively success profiles by means of a set of rules describing the patterns of the most profitable companies.